Hubungan Hitung CD4 dengan Infeksi Cryptosporidium pada Pasien HIV AIDS - Atika Nurmasari Dewi; Rika Nilapsari; Julia Hartati (Bandung Conference Series: Medical Science, 2022)
Abstract. Human immunodeficiency virus (HIV) is a virus that can attack CD4 lymphocytes and cause immune cell death, resulting in severe immune deficiency in infected individuals. When there is a decrease in immunity to CD4 count <200 cells/µL, it is as known Acquired Immunodeficiency Syndrome (ADIS) which can cause opportunistic infections, one of which is Cryptosporidium infection. This study aims to determine the CD4 count and analyze the relationship between CD4 count and the incidence of infection Cryptosporidium infection in HIV/AIDS patients using the Scoping Review method which was carried out by analyzing articles published in 2011-2021 in four database, namely Pub Med, Springer Link, Proquest, and Science Dircet with the types of cohort, cross-sectional, and case control studies published in the last 10 years. The articles obtained were 5212 articles and those that matched the inclusion criteria were 377 articles. After making adjustments to the exclusion criteria, and testing the feasibility using a critical analysis of the Joanna Brigs Institute checklist based on PICOS, 11 articles were found. The result of the analysis of all articles stated that there was a relationship between decreased CD4 count and Cryptosporidium infection, and it was hinger in CD4 count <200 cells/ µL .The result of a decrease in CD4 count is an opportunity for intestinal parasitic infection, especially opportunistic parasitic infections. Decreased CD4 count can cause a decrease in the defense system of the intestinal mucosa, thus facilitating microbial invasion, including Cryptosporidium infection. The conclusion of this study is that by decreasing the CD4 count, Cryptosporidium infection will increase in people with HIV/AIDS. Abstrak. Human Immunodeficiency virus (HIV) merupakan virus yang dapat menyerang limfosit CD4 dan menyebabkan kematian sel imun, sehingga dapat terjadi defisiensi imun yang parah pada individu yang terinfeksi. Pada saat terjadi penurunan imun hingga hitung CD4<200 sel/µL dinamakan sebagai Acquired immunodeficiency Syndrome (AIDS) yang dapat menimbulkan infeksi oportunistik salah satunya adalah infeksi Cryptosporidium. Penelitian ini bertujuan untuk mengetahui hitung CD4 dan menganalisis hubungan hitung CD4 terhadap kejadian infeksi Cryptosporidium pada pasien HIV/AIDS dengan menggunakan metode Scoping Review yang dilakukan dengan cara menganalisis artikel yang dipublikasikan pada tahun 2011-2021 pada empat database yaitu Pub Med, Springer Link, Proquest, dan Science Direct dengan jenis penelitian cohort, cross-sectional, dan case control yang terbit 10 tahun terakhir. Artikel yang didapatkan sebanyak 5212 artikel dan yang sesuai dengan kriteria inklusi berjumlah 377 artikel. Setelah dilakukan penyesuaian dengan kriteria eksklusi, dan uji kelayakan menggunakan telaah kritis dari checklist Joanna Brigs Institute berdasarkan PICOS didaptakan 11 artikel. Hasil analisis dari seluruh artikel menyatakan terdapat hubungan antara menurunnya hitung CD4 dengan infeksi Cryptosporidium, dan lebih tinggi terjadi pada hitung CD4<200 sel/µL. Akibat dari penurunan hitung CD4 merupakan peluang terkenanya infeksi parasit intestinal, terutama infeksi parasit oportunistik. Penurunan hitung CD4 dapat menyebabkan menurunnya sistem pertahanan pada mukosa intestinal, sehingga memudahkan terjadinya invasi mikroba termasuk infeksi Cryptosporidium. Simpulan dari penelitian ini adalah dengan menurunnya hitung CD4 maka infeksi Cryptosporidium akan meningkat pada penderita HIV/AIDS.